IPR CATUARA TM – new cultivar of high gluten wheat - Carlos Roberto Riede; Luiz Alberto Cogrossi Campos; Lauro Akio Okuyama; Maria Brígida dos Santos Scholz; Pedro Sentaro Shioga; Jose Nilvado Póla; Juarez Campolina Machado; Deoclecio Domingos Garbuglio (Crop Breeding and Applied Biotechnology, 2015)
The wheat cultivar IPR Catuara TM, obtained from a cross between the line LD 975 and the cultivar IPR 85, exhibits high gluten strength, which will allow the milling industry to supplement flours from wheats with weaker gluten strength, resulting in better quality products for the final consumer.